Associations between acculturation, ethnic identity, and diet quality among U.S. Hispanic/Latino Youth: Findings from the HCHS/SOL Youth Study. (1st October 2018) - Arandia, Gabriela; Sotres-Alvarez, Daniela; Siega-Riz, Anna Maria; Arredondo, Elva M.; Carnethon, Mercedes R.; Delamater, Alan M.; Gallo, Linda C.; Isasi, Carmen R.; Marchante, Ashley N.; Pritchard, David; Van Horn, Linda; Perreira, Krista M.
Abstract: Background: Acculturation among Hispanic/Latinos has been linked to deteriorating dietary quality that may contribute to obesity risks. This study examined the relationship between acculturation, ethnic identity, and dietary quality in U.S. Hispanic/Latino youth. Methods: This cross-sectional study included 1298 Hispanic/Latino youth ages 8–16 from the Hispanic Community Health Study/Study of Latino Youth (HCHS/SOL Youth), an ancillary study of offspring of participants in the adult HCHS/SOL cohort. Multivariable regression analyses assessed relationships between acculturation and ethnic identity with dietary quality as measured by Healthy Eating Index (HEI) scores, accounting for covariates, design effects, and sample weights. We also compared HEI scores by immigrant generation and language of interview. Results: Youth were 12 ± 2.5 -years and 49.3% female. They were placed into five acculturation categories—including 48% integrated (bicultural orientation), 32.7% assimilated (high U.S. and low Latino orientation), 5.9% separated (high Latino and low U.S. orientation) or marginalized (neither U.S. nor Latino orientation), and 13.3% unclassified. Mean HEI was 53.8; there were no differences in HEI scores by acculturation category, but integrated youth had higher whole grains scores, lower sodium scores, and lower empty calories scores compared to assimilated youth. There were no differences in HEI scores by ethnic identity scores, and no consistent trend between dietary quality and ethnic identity. First- and second-generation youth had higher HEI scores, compared to third-generation youth, and, Spanish-speaking youth had higher HEI scores compared to English-speaking youth. Conclusion: Results suggest that integrated youth in the U.S. may engage in healthier eating behaviors than those who are assimilated. Additional research on Hispanic/Latino youths' acculturation and diet can inform health promotion efforts to improve eating habits and health outcomes among this population.